Pulse height measurements and electron attachment in drift chambers operated with Xe,CO2 mixtures - Andronic, Anton; Appelshäuser, Harald; Braun-Munzinger, Peter; Emschermann, David; Herrmann, Norbert; Mahmoud, Tariq; Reygers, Klaus; Schicker, Rainer; Soltveit, Hans Kristian; Stachel, Johanna; Wessels, Johannes P.; Windelband, Bernd (Nuclear instruments & methods in physics research. Section A, Accelerators, spectrometers, detectors and associated equipment, 2002)
We present pulse height measurements in drift chambers operated with Xe,CO2 gas mixtures. We investigate the attachment of primary electrons on oxygen and SF6 contaminants in the detection gas. The measurements are compared with simulations of properties of drifting electrons. We present two methods to check the gas quality: gas chromatography and 55Fe pulse height measurements using monitor detectors.